A Caputo-Type Fractional-Order SQIRV Mathematical Model for Omicron Variant (Contemporary Mathematics, 2023)
In this study, we propose a fractional-order epidemic model of the Omicron variant. We provide analyses of the solutionʼs positivity, boundedness, existence, and uniqueness. The steady-state solution of the proposed model is asymptotically stable and depends on the reproduction number, R0, which is used to determine whether the disease continues to spread. Numerical simulations are investigated using various orders of the fractional derivative.
Keywords: Omicron; steady-states; reproduction number; stability; Caputo fractional derivative